A Study to Assess the Impact of Structured Teaching Programme on Knowledge and Skill Regarding Self-monitoring of Blood Glucose Level for Prevention of Hypoglycemia among Type 2 Diabetes Mellitus Patients in Endocrinology Ward of Skims Soura - Manzoor, Foziya (International Journal of Nursing and Medical Investigation, 2024)
Aim: The aim of the study was to assess the impact of structured teaching programme on knowledge and skill regarding self-monitoring of blood glucose (SMBG) level for prevention of hypoglycemia among Type-2 diabetes mellitus patient. Materials and Methods: Quantitative research approach with pre-experimental one group pre-test post-test design was used to assess the knowledge and skill regarding SMBG level for prevention of hypoglycemia among 50 Type 2 diabetes mellitus patients in endocrinology ward of Sher - i - Kashmir Institute of Medical Sciences, Soura. Purposive sampling technique was used. Data were collected using structured interview schedule and observational checklist. Results: The study revealed that mean pre-test knowledge and skill scores were 25.8 and 4.72, respectively, and mean post-test knowledge and skill scores were 37.21 and 14.68, respectively. The mean difference between pre- and post-test knowledge and skill score was 11.41 and 9.96, respectively, with P = 0.001 and 0.000, respectively. The results also revealed that there was a significant association between the gender, educational status, family monthly income of the study subjects with the pre-test knowledge, whereas no significant association was found between age and duration of illness. The results also revealed that there was a significant association between the educational statuses of the study subjects with the pre-test skill, whereas no significant association was found between age, gender, family monthly income, and duration of illness. Conclusion: The findings of the study concluded that structured teaching programme was effective in improving the knowledge and skill scores of study subjects.